Estudos reprodutivos, citogenéticos na população de Rhamdia quelen (pisces, Rhamdiidae) do Rio Uberabinha no município de Uberlândia - MG e desenvolvimento de sistema artesanal de recirculação d àgua para criação de peixes - Guilherme, Luiz Carlos (2005)
The Uberabinha river in Uberlândia MG, with an urban area predominancy, in its ichthyofauna composition, presents an expressive fish specimens number. It is detached Rhamdia quelen (Jundiá catfish) as a survivor to the city development process and consequently to the pollution. This specie perform an important ecological role, it is eaten up by part of the population and it seems to be promissory for the regional fish culture. The study of some zootecnical and biological aspects of interest about the specie, detaching the artificial induction of ovulation and fry production from captured reproducers directly from the bed of the river; the evaluation of parent s effects through out the progeny raised in three different stocking densities; knowing the performance of a fish breeding system with water recirculation and biological treatment of metabolic residues and study the cytogenetic aspects in this population are the purposes of this paper. The answer for the ovulation induction and consequently the artificial reproduction were positive and could be obtained a great viable fry number with a pronounced variability in the studied characters. The experiment done to show the parent s effects throughout the progeny raised in three stocking densities lasted 127 days. It has been observed that it didn t have a significative effect between parents concerning length (p>0.01) and weight (p>0.01). The average survival differences were statistically significant for density and parents. The interaction between parents and density was significant concerning length, weight and survival (p<0,01). It has been built a fish system production using a glass fiber box attached to an aerobic reactor for metabolic residues elimination and two models of automatic feeders. Not only the aerobic reactor but also the automatic feeders were done manually. Due to the practical handling, low price and building facilities, the use of this recirculation system for fish production attached to an aerobic reactor and automatic feeder can be recommended for activities developed in research laboratories, fry production unites and familiar breeding. In the system standardization it has been used the tilapia, Oreochromis niloticus, because it is a world wide breed specie, and because the ammonia parameters (TAN), dissolved oxygen (OD), temperature, alkalinity and pH are known for its better performance and being considered to have an excellent growing in this system (EBELING et al., 1995). Its cultivation lasted 260 days using seven trials. In the first six trials the average inicial weight was 1.5g and obtained a net production of 11,345kg, something equal in value of 55,013 kg / m3 / year. In the seventh trial the tilapia s fries with an inical weight of 1.19g lasting 30 thirty days resulted in 1,018Kg netweight of equal value 38,170 kg/ m3 / year. Rhamdia quelen (jundiá catfish), Clarias gariepinus (african catfish) and Leporinus sp (piavuçu), also have been bred. The cytogenetic constitutes an excellent analysis tool to understand the alterations occurred in the chromosomic number and structure. The R. quelen karyotype is composed of 2n=58 chromosomes (26M + 20SM + 8ST + 4A) ranging from zero to seven B chromosomes which ones were stained using the C banding technique and showed themselves total or partially heterochromatic. The chromosomes characterization with Nuclear Organizing Regions, throughout Silver nitrate staining evidenced the presence of one chromosome methacentric pair presenting the Nuclear Organizing Region (NOR), with size polimorphism in its constitution.